Coffee Grounds Reducing Chemical Oxygen Demand (Cod) Levels In Doorsmeer Waste In Gampong Bineh Blang Ingin Jaya District, Aceh Big District - Hamdani, Hamdani; Sudiarto, Dwi (Aceh Sanitation Journal, 2025)
Doorsmeer waste contains high chemical oxygen demand which results in a lack of dissolved oxygen in the water. To reduce chemical oxygen demand levels, this research uses activated charcoal from coffee grounds as an adsorbent because it can trap pollutant particles and is able to adsorb metals, dirt/dust, and detergent foam originating from doorsmeer waste. This research aims to determine the effectiveness of coffee grounds activated charcoal adsorbent in reducing chemical oxygen demand levels in doorsmeer waste. This research was experimental with 3 treatments using 10 gr, 20 gr and 30 gr coffee grounds activated charcoal with 3 repetitions. The subject in this research was a dose of 180 grams of activated charcoal from coffee grounds and the object in this research was doorsmeer waste. On an average decrease in the use of 10 grams of activated charcoal coffee grounds the results were 173.33 mg/l, on an average decrease in the use of 20 grams of activated charcoal coffee grounds the results were 229.33 mg/l, and on an average decrease in use 30 grams of activated charcoal from coffee grounds yielded 263 mg/l. The research results show that the use of activated charcoal from coffee grounds is the most effective in reducing chemical oxygen demand levels in doorsmeer waste, namely a dose of 30 grams with a reduction of 263 mg/l. It is hoped that further research during the process of making activated charcoal will first pay attention to how to make activated charcoal properly and correctly, especially when burning coffee grounds because this greatly influences the quality of the activated charcoal.